A retrospective drug utilization review on the use oftopical corticoteroids for atopic dermatitis in pediatric patients in a tertiary care hospital in the Philippines - Katapang, Laura Christine C.; Pineda, Josela Marie Isabel C.; Tancao, Justine Sofia V.; Ayran, Charles Mandy G. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2023)
Atopic dermatitis (AD) is a chronic disorder of the skin that usually manifests in children. Among the pharmacologic interventions. topical corticosteroids (TCS) are the mainstay anti-inflammatory therapy. However. medication therapy problems (MTP) on prescribers use of steroids have been noted in previous studies such as deviations from the guidelines. Hence. this drug utilization review aims to evaluate the physicians' prescribing patterns of TCS for AD in pediatric patients. A retrospective review of patient charts was conducted in the pediatrics department of a tertiary care hospital for 3 years. All patients diagnosed with AD and were prescribed TCS were included. The prescribing patterns of TCS were reviewed and compared to the local guidelines to determine MTP. Statistical analyses were conducted to determine which factors are associated with the occurrence of MTP. A total of 51 charts were reviewed, and the results revealed that patient cases were usually of mild (29%) and moderate (24%) severity. Weak potency (57%) was the most prescribed, specifically Hydrocortisone acetate (49%), and the most preferred vehicle was cream (53%). During initial consultations, 35% of patient charts had MTPs with dose too high being the most common problem (31%). Statistical analyses revealed that weak, medium, and strong potencies, Clobetasol propionate and Hydrocortisone acetate. and ointment had significant associations with the occurrence of MTPs. Although the majority of charts complied with the guidelines. it is important to note the deviations causing MTPs for better optimization of therapy such as co-management between physicians and pharmacists and patient counseling by dispensing pharmacists.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, August 2023
Keywords: Dermatitis, Atopic. -- Patients; Corticosteroids -- Utilization Review -- Philippines .